Overview of Engineering Options for Increasing Infrastructure Resilience in the Caribbean : 360° Resilience Background Paper - Miyamoto International, Inc. (World Bank, Washington, DC, 2021)
The geographical location of Caribbean counties makes them particularly vulnerable to natural hazards. Buildings, water, transport, and power infrastructure represent key assets for these countries, yet many of these assets are located in highly hazard-prone zones and thus are exposed to the resulting hazard impacts. The continuous operation of critical public buildings, water, transport, and power infrastructure allows for ongoing economic growth and societal well-being. Damage to these sectors results in direct economic losses, operation interruption, and has cascading effects on other infrastructure. To enhance the resiliency of this critical infrastructure, it is important to undertake an evaluation program (condition assessment), identify the vulnerable components, and devise effective strengthening techniques for vulnerable components; the goal of such a program is a reduction in damage, economic losses, and downtime in future natural hazard events.